Interstitial Adipocytes in the Beagle Dog and New Zealand White Rabbit Choroid Plexus. (June 2019) - Rudmann, Daniel; Colleton, Curtis
The choroid plexus (CP) produces cerebrospinal fluid and has epithelial, interstitial, and vascular compartments. The CP is a potential site of toxicity, and recognizing the normal microanatomy in different animal models is important for the pathologist. In preclinical studies with beagle dog and New Zealand white rabbits, we observed variable numbers of adipocytes in the CP interstitium of control and xenobiotic-treated animals. The adipocytes were unilocular and consistent morphologically with white adipose tissue. There was a striking variability in the number of adipocytes; however, the presence of adipocytes was not associated with other microscopic findings that would suggest a pathologic process. The morphology of adipocytes was reminiscent of what is observed normally in the interstitium of other tissues like skeletal muscle, bone marrow, and the subcutis. Therefore, we propose that the interstitial adipocytes not be recorded as a finding in preclinical studies unless the adipocytes are altered spontaneously (ie, lipoma) or after xenobiotic treatment.